2017
DOI: 10.1111/josh.12476
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Electronic Bullying and School Absenteeism Among High School Students in the United States

Abstract: BACKGROUND:We examined the relationship between exposure to electronic bullying and absenteeism as a result of being

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 32 publications
3
32
0
7
Order By: Relevance
“…Second, we could not account for other potential predictors (eg, bullying, environment) that were not available in the MEPS database. Recent studies showed electronic bullying and particular matter air pollution are associated with chronic absenteeism . Therefore, these potential risk factors should be considered to predict chronic absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we could not account for other potential predictors (eg, bullying, environment) that were not available in the MEPS database. Recent studies showed electronic bullying and particular matter air pollution are associated with chronic absenteeism . Therefore, these potential risk factors should be considered to predict chronic absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient was unwilling to go to school, and her academic performance had declined. Poor attendance due to unwillingness to attend and fear of school has been shown to be significantly associated with cyber bullying (Grinshteyn & Yang, ). Although cyber bullying resembles traditional forms of bullying, it also exhibits potentially threatening differences.…”
Section: Discussionmentioning
confidence: 99%
“…Victims have demonstrated loneliness and depressive mood (Olenik-Shemesh, Heiman, & Eden, 2012) lower self-esteem and higher levels of depression and suicide . Cyber victimisation has also been linked to school absenteeism and academic problems (Grinshteyn & Yang, 2017;Tsitsika et al, 2015). Being a cyber bully has been linked to conduct problems, low prosocial behaviour and not feeling safe in school (Sourander et al, 2010), while bully-victims are shown to have increased risk of mental health problems (Kowalsi & Limber, 2013).…”
Section: Consequences Of Bullying and Cyberbullyingmentioning
confidence: 99%